Mesleki müzik eğitimi veren kurumlarda performans kaygısı ve öz-yeterlik algısının çalgı başarısına etkisi - Işkın, Selda (My University, 2018)
Bu araştırma, mesleki müzik eğitimi veren farklı kurumlarda öğrenim gören öğrencilerin performans kaygısı ve öz-yeterlilik algısının çalgı başarısına etkisini incelemek amacıyla yapılmıştır.Araştırma, tarama modeline uygun olarak düzenlenmiştir. Araştırmanın örneklemi, Marmara Üniversitesi Atatürk Eğitim Fakültesi, Kocaeli Üniversitesi Güzel Sanatlar Fakültesi ve İstanbul Üniversitesi Devlet Konservatuarı öğrencilerinden oluşan toplamda 242 kişi oluşmaktadır.Araştırmada kullanılan ölçekler, Kişisel Bilgi Formu, Çalgı Performansı Öz-yeterlik İnancı Ölçeği ve Kenny Müzik Performans Kaygısı Envanteri’dir.Araştırmadan elde edilen verilerle ilgili yapılan analizler, Kişisel Bilgi Formu, Kenny Müzik Performans Kaygısı Envanteri ve Çalgı Performansı Öz-yeterlik İnancı Ölçeği ile toplanmış ve verilerin tümü “SPSS 23.0 for Windows” paket statistiksel analize tabi tutulmuştur. Araştırmanın amacına uygun olarak belirlenen analizlere geçilmeden önce, verilerin belirlenen sınırlar içinde olup olmadığı, hata ve eksiklikler taşıyıp taşımadığına bakılmış bundan sonra ise ölçek ve boyut puanlarının Kolmogorov-Smirnov (K-S) testi ve çarpıklık/ basıklık değerlerine bakılarak normallik dağılımları incelenmiştir.Araştırmada elde edilen bulgular, araştırmaya katılan öğrencilerin, negatif performans algısının öğrenim gördükleri programa göre anlamlı bir farklılık gösterdiğini ve a) Eğitim Fakültesi öğrencilerinin, negatif performans algısı düzeylerinin, diğerlerinden daha yüksek olduğunu b) Güzel Sanatlar Fakültesi öğrencilerinin negatif performans algısı düzeylerinin ise Konservatuar öğrencilerinden daha yüksek olduğunu göstermiştir. Öğrencilerin, çalgı performansı öz-yeterlik inanç düzeylerinin (puanlarının) öğrenim gördükleri programa bağlı olarak anlamlı bir farklılık göstermediği bulunmuştur (p>0.05).

This research was carried out to investigate the effect of performance anxiety and self-efficacy to the instrumental performance of the students who were educated in different institutions providing professional music education.The research was designed according to survey model. The samples of the research consisted of 242 people who are students in Marmara University Atatürk Faculty of Education, Kocaeli University Faculty of Fine Arts, and Istanbul University Conservatory.Personal Information Form, Instrumental Performance Self-Efficacy Scale, and Kenny Music Performance Anxiety Inventory are the scales used in this research.Analyses of the data which was obtained from the study were collected with the Personal Information Form, Instrumental Performance Self-Efficacy Scale, and Kenny Music Performance Anxiety Inventory and all the data was analysed statistically with the “SPSS 23.0 for Windows” package program. Before proceeding with the analyses determined as appropriate for the purpose of the study, it was observed whether the data were within the specified limits, whether there were errors or deficiencies. After this, the normality distributions of the scale and dimension scores were examined by looking at Kolmogorov-Smirnov (K-S) test and skewness/ kurtosis values.Findings obtained from the research demonstrated that the negative perception of performance of students who participated in this research have a meaningful correlation according to their education program; furthermore, a) Students of the Faculty of Education have a higher negative perception level than others, b) The level of negative performance perception of the students of the Faculty of Fine Arts was higher than the Conservatory students. It was found that students did not show any significant difference in musical performance self-efficacy belief levels (scores) depending on the program they study (p>0.05).
Keywords: Eğitim ve öğretim; Instruction and study; Kaygı; Music; Müzik; Öz-yeterlik; Öz-yeterlik Algısı Anxiety; Performance Anxiety; Performans Kaygısı; Self-efficacy; Self-efficacy Perception; Turkey; Türkiye